Outcome of Glansectomy and Skin Grafting in the Management of Penile Cancer - Hugh F. O'Kane; Ajay Pahuja; K. J. Ho; Ali Thwaini; Thaigarajan Nambirajan; Patrick Keane (Advances in Urology)
Purpose. To report outcome data for patients with penile cancer treated surgically with glansectomy and skin grafting. Materials and Methods. We retrospectively reviewed data on all patients undergoing surgical management of penile cancer by a single surgeon between 1998 and 2008. Outcomes in patients who underwent glansectomy and skin grafting were analysed. Results. Between 1998 and 2008 a total of 25 patients with a mean age 60 (39–83) underwent glansectomy and skin grafting. Six patients had carcinoma in situ (CIS); the stage in the remaining patients ranged from T1G1 to T3G3. Mean followup for patients was 28 months (range 6–66). Disease specific survival was 92% with 2 patients who had positive nodes at lymph node dissection developing groin recurrence. One patient developed a local recurrence requiring a partial penectomy. Conclusions. Penile preserving surgery with glansectomy and skin grafting is a successful technique with minimal complications for local control of penile carcinoma arising on the glans. Careful followup to exclude local recurrence is required.